PAIGC : A face do monopartidarismo na Guiné-Bissau (1974 a 1990) - Semedo, Rui Jorge da Conceição Gomes (2009)
This research investigates the political dynamics of PAIGC (African Party for the Independence of Guinea and Cape-Verde), that during and after the process of getting the independence from the portuguese, wich was done through a long liberation war, has a tremendous help from the mass. PAIGC officially conquered the political power in 1974 and ruled for a period or 16 year, as a sole political party. During this period, it showed a lot of dificulties to realize its program of governance. This fact leads to a fundamental question: how come that a party that counted with a strong base of help from the mass and acted as a sole political force that controlled the machinery oh the state was not able to implement its proposals of governance?